Civil society in Europe : minimum norms and optimum conditions of its regulation - Ploeg, T. J. van der; Versteegh, Cornelia R. M. (Cambridge University Press, 2017)
This book explores how civil society organisations are, and might best be, regulated in Europe, at both the regional and domestic level.